Adjuvant systemic chemotherapy for HER2-Negative disease - Kilic, Leyla; Aydiner, Adnan (Springer International Publishing, 2016)
Breast cancer is a heterogeneous, phenotypically diverse disease comprising several biological subtypes with distinct behaviors and responses to therapy. All patients with invasive breast cancer should be evaluated to assess the need for adjuvant cytotoxic therapy, trastuzumab, and/or endocrine therapy. If patients must receive endocrine therapy (either tamoxifen or aromatase inhibitor) and cytotoxic therapy as adjuvant therapy, chemotherapy should precede endocrine therapy. The pathology report must provide uniform information about the tumor and should include at a minimum the parameters recommended in the ASCO-CAP guideline. Molecular subtypes of breast cancer can be distinguished by common pathological variables, including estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor (HER2), and Ki67 index. The inclusion of chemotherapy in the adjuvant regimen depends on the intrinsic subtype. Multigene expression array profiling is not always required for subtype definition after clinicopathological assessment. Young age, grade 3 disease, lymphovascular invasion, one to three positive nodes, and large tumor size are not adequate features to omit molecular diagnostics in the decision of adjuvant chemotherapy. Any lymph node positivity should not be a sole indication for adjuvant chemotherapy. However, patients with more than three involved lymph nodes, low hormone receptor positivity, positive HER2 status, triple-negative status, high 21-gene RS (e.g., >25), and high-risk 70-gene scores should receive adjuvant chemotherapy. A high Ki67 proliferation index and histological grade 3 tumors are acceptable indications for adjuvant chemotherapy. For women desiring fertility preservation and for patients with certain comorbidities such as cardiovascular disease and diabetic neuropathy, specific chemotherapy regimens may be preferred. © Springer International Publishing Switzerland 2016.
Keywords: Adjuvant; Basallike; Chemotherapy; Elderly; EndoPredict; Genomic grade index; Grade; Immunohistochemistry; Ki67; Luminal A; Luminal B; MammaPrint; Multigene; Obese; Oncotype DX; PAM50; Pregnancy; Theros; Triple negative